ALBAYEN IN FOCUS: REVOLUTIONIZING ISLAMIC EDUCATION IN MALAYSIA - AN ANALYSIS OF TEACHER AND STUDENT ACCEPTANCE AND BENEFITS - Latif, Adibah Abdul; Wahidah, Finadatul; Abdelhedi, Amine; Arsat, Mahyudin; Yusof, Farahwahida Mohd; Jumaat, Farhana (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
This study explores the Albayen educational platform, a pioneering initiative in integrating technology with Islamic education content. Launched in Malaysia and subsequently extended to other Southeast Asian countries, Albayen represents a significant shift towards a comprehensive, adaptable, and technologically infused approach in Islamic educational settings. Employing a case study methodology, this research focuses on three Islamic religious schools in Johor, Malaysia. It encompasses the experiences of 30 teachers and 152 students, utilizing a mixed-method approach comprising interviews and questionnaires. This methodology provides a holistic view of Albayen's implementation and its effects on pedagogical practices and learning experiences. Findings indicate that Albayen has substantially enhanced both technological and pedagogical skills among teachers. Most reported significant improvements in technical skills and teaching methodologies, reflecting Albayen's effectiveness in modernizing educational practices. For students, Albayen has notably increased motivation and enriched learning experiences, with over 85% reporting high levels of engagement and enhanced understanding. In conclusion, Albayen emerges as a transformative tool in Islamic education, effectively bridging traditional practices with modern digital approaches. Its impact on teaching quality and student learning experiences suggests its potential as a model for global Islamic education reform in the digital age.